2016
DOI: 10.1159/000446904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Classification of Cerebellar Foliation in Cartilaginous Fishes (Class: Chondrichthyes) Using Three-Dimensional Shape Analysis and Its Implications for Evolutionary Biology

Abstract: A true cerebellum appeared at the onset of the chondrichthyan (sharks, batoids, and chimaerids) radiation and is known to be essential for executing fast, accurate, and efficient movement. In addition to a high degree of variation in size, the corpus cerebellum in this group has a high degree of variation in convolution (or foliation) and symmetry, which ranges from a smooth cerebellar surface to deep, branched convexities and folds, although the functional significance of this trait is unclear. As variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
(154 reference statements)
0
10
0
Order By: Relevance
“…Morphologically, the corpus cerebellum varies substantially in size, level of convolution (a.k.a. foliation) and symmetry in cartilaginous fishes 27,30,74,134136 , and it has been suggested that this may reflect performance differences in cerebellar-dependent functions and behaviors 132 . Both S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologically, the corpus cerebellum varies substantially in size, level of convolution (a.k.a. foliation) and symmetry in cartilaginous fishes 27,30,74,134136 , and it has been suggested that this may reflect performance differences in cerebellar-dependent functions and behaviors 132 . Both S .…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution (100 μm isotropic), T1-weighted images were acquired using a 3D FLASH sequence with RF spoiling. Images were produced with high contrast between gray and white matter in cartilaginous fish brains 86,136 , from which structural characteristics were derived (Fig. 2A,B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model order has physical significance as a measure of an objects complexity, and consequently can have biological and evolutionary significance, as was demonstrated in our study to characterize of cerebellar foliations in elasmobranch brains [73], which has implications in the quantification and comparison of the cerebellum in different species of elasmobranchs where variation in cerebellar foliations has been shown to be related to species habitat and predation strategies and has evolutionary significance [74][75][76].…”
Section: The Model Order Problemmentioning
confidence: 96%
“…We fit, then get segmentation afterwards, essentially “for free”. Moreover, an important practical aspect of this method is that the entire process takes on the order of 12 s, whereas that of the “standard” method takes about 12 h. This method has been used to quantitatively classify cerebellar foliation in cartilaginous fishes (eg, sharks) which has important implications for evolutionary biology, and for cortical thickness measurements in Alzheimer’s Disease. It is also at the heart of our entire suite of programs.…”
Section: Theorymentioning
confidence: 99%